Which eye are you looking through? The impact of cognitive bias on process safety. Issue 1 (10th June 2021) - Kerin, Trish
Abstract: Bias surrounds us every day. Everything we look at has a lens of our experience coloring our perception, and everyone has their own lens. This impacts how we share and receive information. So why is this important for process safety? Cognitive biases cover a range of aspects, each of which can have an impact on process safety, from what we remember, to coping with too much information, to a lack of context and meaning or a need to act with great haste. There are many identified specific cognitive biases, not every one of them impacts on process safety, but many can and have. This paper will review several process safety type incidents that had cognitive bias as a factor and discuss ideas on how to manage the bias, so we do not fall into its trap.